2018
DOI: 10.1007/s00330-018-5643-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of initial enhancement analysis using ultra-fast dynamic contrast-enhanced MRI for breast lesions

Abstract: • Ultra-fast dynamic MRI effectively differentiates benign from malignant breast lesions. • Ultra-fast dynamic MRI contributes to BI-RADS categorisation in non-mass enhancement. • Management of non-mass breast lesions becomes more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 37 publications
6
48
0
Order By: Relevance
“…Some previous studies showed the discriminating power of the MS and TTE when adopting UF‐DCE MRI with a view‐sharing technique, while there remains limited data for CS. Owing to better image quality achieved by CS, our data showed the value of UF‐DCE MRI for not only a kinetic evaluation but also a morphological evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous studies showed the discriminating power of the MS and TTE when adopting UF‐DCE MRI with a view‐sharing technique, while there remains limited data for CS. Owing to better image quality achieved by CS, our data showed the value of UF‐DCE MRI for not only a kinetic evaluation but also a morphological evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrafast DCE (UF‐DCE) MRI is an attempt to extract both morphologic and kinetic information in the early postcontrast period, and thus capture the inflow of contrast in breast lesions. Most studies have used reconstruction techniques, such as view sharing or compressed sensing (CS), to achieve high spatial and high temporal resolution, and thus acquire images with high spatial resolution at many timepoints in the early postcontrast period …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathological and pharmacokinetic mechanisms differed in benign and malignant lesions. Malignant tumors had abundant vascularity and highly permeable vessel walls that allowed easier transfer of the contrast agent from vessels to the extravascular space was easier; thus, malignant lesions had shorter TTE and larger MS, while the benign lesions showed the opposite ndings [32,33]. This could explain why in the combined model, the texture features extracted from the 2nd and 5th contrast sequences were independently relevant to discriminate benign and malignant NME.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic accuracy was also improved when data from the initial enhancement analysis was combined with conventional BI-RADS categorization, compared with BI-RADS alone, especially for non-mass breast lesions (3). Moreover, screening results using breast ultrafast DCE-MRI showed higher specificity, shorter reading times, and non-inferior accuracy compared to full diagnostic MRI (4).…”
Section: Introductionmentioning
confidence: 97%